2014
DOI: 10.1080/1550428x.2014.964442
|View full text |Cite
|
Sign up to set email alerts
|

Online Coming-Out Communications Between Gay Men and Their Religious Family Allies: A Family of Choice and Origin Perspective

Abstract: Gay men use social networking sites and blogs more than heterosexual men (Harris, 2010). However, little is known about how they communicate online while coming out. Yet, coming out often results in a loss of social support for gay youths from religious backgrounds, suggesting that alternative supports such as families of choice and online networks may be particularly beneficial (Saltzburg, 2007). The present study addresses this gap by focusing on how gay emerging adults (N = 23) and their religious family al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…For instance, participants reported a number of benefits to coming out online (e.g., increased authenticity), and generally described their experiences as positive and socially supportive. These findings contribute to a growing body of literature that suggests that gay men may experience social and mental health benefits as a result of their online experiences with others (Etengoff & Daiute, 2014).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…For instance, participants reported a number of benefits to coming out online (e.g., increased authenticity), and generally described their experiences as positive and socially supportive. These findings contribute to a growing body of literature that suggests that gay men may experience social and mental health benefits as a result of their online experiences with others (Etengoff & Daiute, 2014).…”
Section: Discussionsupporting
confidence: 61%
“…For example, Etengoff and Daiute (2014) found that 7 out of 15 gay Facebook users used the website as a tool to come out. Another study (Anderson, 2011) found that gay college athletes utilized Facebook as a means to disclose their sexual identity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, transgender individuals living in rural communities with limited-to-no access to transgender support groups, counseling, and clinics may be using transvlogs as a social support and educational resource. Transgender individuals without biological familial support may find it to be helpful to use transvlogs to create a non-biological, family of choice community (for more information on family of choice models see Etengoff & Daiute, 2015).…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…LGBTQ online communication Technological systems such as YouTube enable people to collaboratively co-create sociotechnical tools-in-practice (Engeström, 2013;Etengoff, 2011;Etengoff & Daiute, 2015). Online communication networks are comprised of people with shared interests who utilize a virtual platform to create accessible, user-generated resources that facilitate companionship and bonding, social activity and interaction, and/or collective efficacy (Rotman & Preece, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have explored the coming out experiences of LGBTI individuals without ASDs in novels (Beck 2013), sports (Billings et al 2015;Kian et al 2015), television shows (Mitchell 2015), and families (Etengoff and Daiute 2015;Jadwin-Cakmak et al 2015). In terms of people with disabilities, there is literature on LGBTI people with intellectual disabilities coming out (Noonan and Gomez 2011).…”
mentioning
confidence: 99%